2016
DOI: 10.1186/s12971-016-0077-8
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to active and passive smoking among Greek pregnant women

Abstract: BackgroundActive smoking and exposure to passive smoke are responsible for numerous adverse pregnancy outcomes for women and their infants. The aim of this study was to explore the perceptions, attitudes, patterns of personal tobacco use and exposure to environmental smoke among a sample of pregnant women in Greece.MethodA cross sectional survey was undertaken of 300 women identified from the perinatal care records of the Maternity Departments of two hospitals in Athens between February 2013 and May 2013. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 36 publications
4
29
3
5
Order By: Relevance
“…Most of the women smoked 1-5 cigarettes a day during this period. (5), and 48% by Vivilaki et al (24), which are higher than that in the present study. In the study on smoking during pregnancy in the low-and middle-income countries by Caleyachetty et al (25), the highest and the lowest rates of smoking were found in South Asia (5.1%) and Africa (2%), respectively .…”
Section: Discussioncontrasting
confidence: 56%
“…Most of the women smoked 1-5 cigarettes a day during this period. (5), and 48% by Vivilaki et al (24), which are higher than that in the present study. In the study on smoking during pregnancy in the low-and middle-income countries by Caleyachetty et al (25), the highest and the lowest rates of smoking were found in South Asia (5.1%) and Africa (2%), respectively .…”
Section: Discussioncontrasting
confidence: 56%
“…Vivilaki et al 38 in Greece indicated that awareness about the health problem for the fetus and attitude to smoke during pregnancy were the main factors in pregnant smoker women. Bahiraii et al 14 reported that presence of a smoking individual and false beliefs of pregnant women about the effects of smoke on the health of the fetus could be important elements to consider in order to improve the prevalence of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that there is strong association between maternal smoking habits during the pregnancy and socioeconomic deprivation (2). Additionally, women whose partners were smokers were more likely to smoke throughout pregnancy (3). Ethnic minority groups, such as Roma in Europe, are disproportionately living in deprived communities, their rates of tobacco use are high, and they experience significant exposure to second hand smoke (SHS) (4).…”
Section: Introductionmentioning
confidence: 99%